MAKNA PERAN AYAH DITINJAU DARI PERSEPSI ANAK YATIM - jusnita sari; Syamsul Bachri Thalib; Aswar Aswar (JURNAL PSIKOLOGI SKIsO (Sosial Klinis Industri Organisasi), 2020)
This study aims to reveal and understand the meaning of the father's role in terms of perceptions of the orphan and its impact. The role of the father is to earn a living for the family, but the role of the father also has an effect on increasing the child's motivation, achievement and academic achievement. This study used a qualitative method with a descriptive approach with three orphans in Bone Regency as the subjects. The results of the study can be concluded that the perception of the role of the father of two out of three subjects tends to have a negative opinion because the subject feels disappointed, the subject understands that the father is a good educator for his child, but in fact the subject often gets physical violence if he makes a mistake without giving advice or direction first. While the perception of one subject tends to be positive because the subject understands the role of the father as the head of the household who is responsible and hardworking, this is in accordance with the expectations of the subject. The psychological impact of orphans can be seen from the perceptual aspects that arise, namely the cognitive component, the affective component and the conative component. Two out of three subjects tend to behave aggressively, get along wrong, less responsible because the subject loses the figure of a guide and educator so that the subject looks for new things in the surrounding environment. Meanwhile, one subject grew into a responsible, hard-working teenager. From the description above, it can be concluded that if the orphan perceives a positive father, the orphan will behave positively and vice versa. Keywords: Perception of orphans, father's role